Contribuições do yoga como proposta terapêutica em sintomas depressivos - Costa, Hérica de Carvalho (2019)
The purpose of this study was to make a relation between the perception of the subjects before and after the practice of Yoga, in order to identify the units of meanings that allowed to report the effects of this body practice, which is the basis of the present investigation, which aim at understanding the phenomenon of depression from the perception of the subject practitioner of Yoga itself. The methodological construction of the study was carried out from a qualitative field research, where a Yoga intervention was carried out at the UBS of Intermares, in the municipality of Cabedelo, Metropolitan Region of João Pessoa - PB. The research had the participation of 3 subjects, women, aged between 47 and 57 years. As a tool for obtaining information regarding participants 'perceptions, a field diary was written, practitioners' notes and their spontaneous reports at the beginning and end of each practice and the free interview. And as technique, the Analysis of the Phenomenon Located. It was observed that the subjects, participants in the Yoga Intervention, realized that the practice helped them positively regarding the relief of depressive symptoms